Arachnoid Cyst and Psychosis: The Troublemaker or Innocent Bystander - Das, Soumitra (Indian J Psychol Med, 2017)
Organic underpinning of a psychotic disturbance is often missed. Arachnoid cysts are considered a rare neurological tumor, few of which exhibit any symptomatology. In most cases, they are diagnosed by accident. Literature regarding the coexistence of arachnoid cysts with psychiatric disorders is sparse. Here, we present a case who presented with a typical presentation of psychosis which was not enough for suspecting for an organic etiology.